Pemberdayaan Masyarakat Desa Cileuksa Dalam Meningkatkan Perekonomian Masyarakat Melalui UMKM - Ari Soeti Yani; Fauziah Fauziah; Rio Johan Putra; Mila Mila (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
This Community Service Program aims to empower the people of Cileuksa Village to improve the community's economy through MSMEs. Cileuksa Village is one of the villages in Sukajaya District, Bogor Regency, West Java Province. In the village of Cileuksa there is also a lack of awareness in managerial business management and tax aspects of MSMEs. Success in managing a business is largely determined by the expertise of business actors in obtaining sources of capital and procedures for managing finances, plus knowledge in terms of regulations such as taxation and related rules in the MSME business sector, such as MSME taxes and regulations regarding goods for consumption must be fulfilled and implemented. Limited knowledge is one of the challenges that must be faced by rural communities in managing their business, so that village MSME businesses can run, it is necessary to have socialization on how to obtain and manage MSME capital and know taxation.